The impact of migrant workers’ remittances on the living standards of families in Morocco: A propensity score matching approach - Bouoiyour, Jamal; Miftah, Amal (Migration Letters, 2015)
This article attempts to assess empirically the impact of remittances on household expenditure and relative poverty in Morocco. We apply propensity score matching methods to the 2006/2007 Moroccan Living Standards Measurement Survey. We find that migrants’ remittances can improve living standards among Moroccan households and affect negatively the incidence of poverty. The results show a statistically significant and positive impact of hose remittances on recipient households’ expenditures. They are also significantly associated with a decline in the probability of being in poverty for rural households; it decreases by 11.3 percentage points. In comparison, this probability decreases by 3 points in urban area.